Fingerprint Image Enhancement In Fingerprint Recognition System - Acharya, Kritika; Mandal, Sandip (IJRDO -Journal of Computer Science Engineering, 2015)
Fingerprints are the oldest and most widely used form of biometric identification. The performance of anyfingerprint recognizer highly depends on the fingerprint image quality. Different types of noises in the fingerprint imagespose greater difficulty for recognizers. Thus, image enhancement techniques are employed prior to minutiae extraction toobtain a more reliable estimation of minutiae locations. An enhancement algorithm improves image quality and repairbroken ridges.This paper proposes a new method of enhancing fingerprint image which improves the visual quality of the fingerprintimage. The result shows, it can improve the performance of image enhancement.